peningkatan KEMAMPUAN BAHASA INGGRIS SISWA KLS xI DALAM MEMBUAT KALIMAT PENGANDAIAN TYPE II MELALUI MEDIA GAMBAR SMA NEGERI 1 RAMBAH - Lariama Tobing (JURNAL PENDIDIKAN ROKANIA, 2019)
This study aims to improve the learning outcomes of English about the material for making type II presuppositions using media images of XI students of IBU 1 in Rambah State High School, Rokan Hulu. Action research was carried out in 2 cycles. Data collection in this study uses test and observation methods. Data from research results on addition and subtraction material were analyzed descriptively quantitative. The results showed that learning using picture media can improve learning outcomes in English in making type II conditional sentences in class XI 1 of IBU State High School I Rambah, which at the initial condition of the results before being given an average score of 56. In cycle I using image media has increased so that the average grade value becomes 62. In the second cycle showed an increase with an average of 79.33.